Acerca de un comentario sobre el rey Wamba (672-680) y la Chronica Naierensis (s.XII) - Martínez Ortega, Ricardo (1997)
A remark by Prof. Juan Gil in his historiographical study of the XI-XIII centuries prompted the writing of this paper, which is an attempt to track down the two current traditions about the figure of king Wamba (672-680). One considers him to be a monk who died in Pampliega (Historia de rebus Hispanie, Chronicon Mundi, Crónica de Alfonso III, Primera Crónica General de España); the other, represented by the Chronica Naierensis, believes him to be buried somewhere in the threefold place-name Castella-Valle Monio-ecclesia Sancti Petri. The author concludes that in fact both interpretations refer to the same place, which in one case is known as Pampliega, a village in Burgos, but also as Saint Peter's church, in Pampliega. No contradiction therefore exists between the old tradition and that ofthe Chronica Naierensis.
Keywords: Wamba, -- Rey de los Visigodos; Crónica najerense